Testes de primalidade: uma análise matemática dos algoritmos determinísticos e probabilísticos - Andrade, Ricardo Pereira de (2017)
This paper presents the main tests of primality through a study on the base mathematics used to guarantee the validity of each method, as well as an analysis of their computational complexity.